Immunomodulatory effect of the hydroalcoholic extract of Abrus precatorius L. leaves against cyclophosphamide-induced immunosuppression in mice - Modi, Chirag M.; Bhatt, Punit R.; Patel, Urvesh D.; Patel, Harshad B.; Pandya, Kajal B. (Archives of Biological Sciences, 2021)
Paper description: The immunomodulatory activity of Abrus precatorius , which is traditionally used to treat different ailments, has not been examined. BALB/c mice were given per os the hydro-alcoholic extract of precatorius leaves against cyclophosphamide-induced immunosuppression. Parameters, including splenocyte proliferation, haemagglutination (HA titer), delayed-type hypersensitivity, interleukin-2 level, neutrophil adhesion and the histopathology of spleen, liver and kidney were examined. The leaf extract stimulated T-lymphocytes, improved HA titer, total protein and interleukin-2 level. precatorius leaves are a good candidate for a new immunomodulatory herbal formulation. Abstract: This study presents the immunomodulatory potential of Abrus precatorius Linn. (Indian wild licorice) leaves. A hydroalcoholic extract of A. precatorius leaves (EAPL) was prepared by maceration. Thirty male mice were divided into five groups as follows: control group, model control group (cyclophosphamide-treated), and three treatment groups (treated with EAPL at doses of 100, 200 and 300 mg/kg, per os, daily for 14 days). Parameters, including hematological, biochemical, organ indices, hemagglutination test (HA titer), delayed-type hypersensitivity (DTH), interleukin-2 (IL-2) level, splenocyte proliferation and liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) analysis were evaluated. Histopathological examination was carried out for the spleen, kidney and liver. Cyclophosphamide (CPMD)-induced changes in white blood cells, lymphocytes and platelets were improved in the treatment groups. Total protein and albumin levels in the treatment groups were significantly higher. EAPL treatment significantly stimulated splenic T-lymphocyte-mediated proliferation. Neutrophil adhesion was insignificantly decreased in the model control group compared to the normal control group, which was slightly improved by EAPL treatment. EAPL treatment significantly improved the HA titer and cell-mediated immunity, which is an indication of antibody production. The IL-2 level was significantly higher in the treatment groups that received 200 and 300 mg/kg EAPL. LC-QTOF-MS analysis of EAPL showed the presence of flavonoids, lignans, iridoids and phenolic glycosides. These results suggest that A. precatorius leaves are a good candidate for a new immunomodulatory herbal formulation.